2009
DOI: 10.1007/s11908-009-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

MRSA infection of buttocks, vulva, and genital tract in women

Abstract: Staphylococcus aureus, although a common commensal bacterium, is a frequent cause of skin and soft tissue infections as well as life-threatening blood stream infections. Resistance to methicillin, which previously was associated with only hospitalized patients, has become a common community-based phenomenon. Less well known is S. aureus vaginal colonization and heterosexual transmission, mainly by skin-mucosa contact. Recognizing the vagina as a reservoir is important and should not be ignored, particularly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Because of the high prevalence of MRSA, antibiotic coverage should include this organism 3. Previous research has documented a high susceptibility of MRSA to trimethoprim-sulfamethoxazole, which also provides coverage to other microbes commonly isolated from the vulva, such as Proteus, E. coli, and group B Streptococcus 7. Duration of therapy is guided by the resolution of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high prevalence of MRSA, antibiotic coverage should include this organism 3. Previous research has documented a high susceptibility of MRSA to trimethoprim-sulfamethoxazole, which also provides coverage to other microbes commonly isolated from the vulva, such as Proteus, E. coli, and group B Streptococcus 7. Duration of therapy is guided by the resolution of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While not a common finding in women's health, CA‐MRSA has been increasingly documented in pregnant women, post‐partum women, heterosexual individuals and men having sex with men. In several small community‐based studies, there was evidence that CA‐MRSA found in the vagina could be another isolated reservoir, opening up the potential for transmission to sexual partners mainly by skin‐mucosa contact (Reichman & Sobel, ). MRSA is most commonly found in the nares, serving as the main source for colonization; there are other areas, however, less known to act as a reservoir that should not be ignored (see Box 6), as the potential for transmission exists if health care providers underestimate the potential for CA‐MRSA to spread via these uncommon routes.…”
Section: Community‐acquired Versus Hospital‐acquired Mrsamentioning
confidence: 99%
“…This is largely attributable to inappropriate usage and prescribing (Charani et al 2011).The case of AR for community acquired methicillinresistant Staphylococcus aureus (CA-MRSA) has become the focus of intense scientific and political interest globally. CA-MRSA is classified by the Centers for Disease Control (CDC) as patients with no prior MRSA infection whose culture was obtained not more than 48 hours before admission (Reichman & Sobel 2009, CDC 2011.…”
Section: Introductionmentioning
confidence: 99%